GEOLOGY AND PROVENANCE OF FM. NGRAYONG SANDSTONE OF NGIYONO AND SURROUNDINGS, BLORA DISTRICT, CENTRAL JAVA - Daniel Adipradipto
Java is a familiar area to many interest of geology including oil and gas exploration. The Rembang-Madura-Kangean-Sakala (RMKS) area is one of the most common studied area in East Java. This research area covers Blora and Rembang district. Research area covering about 66 km2 is composed to six formations, according to Peta Badan Geologi. Researcher found six litology units which can be differed descriptively in the field, they are Limestone I, Sandstone, Limestone II, Claystone, Limestone III, and Marl unit. These six units are Early Miocene to Holocene Age. The study area also has some geological structures, they are fold, strike-slip fault, normal fault, and faultbend fold. There is also a study of provenance of sandstone of Ngrayong Formation. Eight samples are classified as Recycled Orogen Provenance (Dickinson and Suczek, 1979).